ANALYSIS OF CUSTOMER SATISFACTION ON THE QUALITY OF PURPLE PATTOM CRUISER USING IMPORTANCE PERFORMANCE ANALYSIS (IPA) METHOD - Whydiantoro Whydiantoro; Budiman Budiman; Engkos Koswara; Intan Kusumadewi (Jurnal Mekanika dan Manufaktur, 2022)
Following up on PKM on purple sweet potato crackers in Padahanten village and seeing the current very rapid development of the service business, with the growth of the service business in Indonesia this has resulted in higher competition, consumers are more selective in buying and choosing the products they need. Therefore, purple sweet potato chips must be able to meet consumer needs. Products that are able to win the competition with competitors need a strategy that can improve services and be able to compete effectively in this increasingly competitive market. Win the competition and keep the business alive, growing and getting as many customers as possible. This can be said to be successful if consumers are satisfied with the performance of a product or service provided by the entrepreneur. According to Lewis & Booms, in Service Management by Fandy Tjiptono (2016) Service quality is defined as a measure of how large the level of service that can be provided in accordance with the level of consumer expectations. In other words, the factors that affect the quality of service are the services expected by consumers, if the service exceeds what is expected by consumers, the quality of service can be said to be good (positive), and vice versa if the service is not in accordance with what is expected by consumers, it can be said that the quality of service is bad. (negative value) Quadrant analysis or Importance Performance Analysis (IPA) is a descriptive analysis technique introduced by John A. Martilla and John C. James (1977) cited by Tjiptono and Chandra (2016: 222-223). Importance Performance Analysis (IPA) is an analytical technique used to identify what important performance factors must be demonstrated by an organization in meeting the satisfaction of their service users (consumers). Therefore, it is necessary to conduct research on the analysis of consumer satisfaction on the quality of service in the marketing of purple sweet potato crackers by using the Importance Performance Analysis (IPA) method. and promotions. Through these (4P's) attributes, it will be known what influences consumers' desire to visit Padahanten purple sweet potato. The variables that are traced or researched are aspects of reliability (reliability), responsiveness (response), tangible (tangible), assurances (certainty), and empathy (empathy).